Profiling Students Learning Styles on Song-Assisted Science Lesson Content to Support Merdeka Belajar - Fahrozi, Ichsan; Sutikno, Putri Yanuarita (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Each student has its own characteristics, especially in terms of learning styles. In that case, teachers as educators must create a learning atmosphere and appropriate media and meet each student's learning needs, according to Merdeka Belajar's goal, which provides flexibility to educators in designing learning. Based on this, this research aims to produce significant data or information about the implementation of song media in science lesson content to fulfill students' learning styles. This type of research is qualitative research. This study uses a case study method to explore reality, applying different learning methods by profiling students' learning styles. The research subjects were teachers and students of grade V. The techniques used to collect data are interviews, observations, and student questionnaires. The data analysis technique used in this study is qualitative descriptive with Miles and Huberman's version of data analysis techniques. The study results show that using song media in science subjects can meet the needs of students' learning styles. The learning style of grade V students includes 21% visual, 48% auditory, and 31% kinesthetic, which can be fulfilled using song media in science subjects.